2018
DOI: 10.1002/ijfe.1660
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the effects of income inequality on financial fragility: Evidence from Organization for Economic Co‐operation and Development countries

Abstract: The main scope of the paper is to investigate the proposition that rising income inequality results in systemic financial instability in developed countries. In particular, 33 OECD (Organization for Economic Co‐operation and Development) countries are studied in a panel Vector Autoregression (VAR) framework analysis over 1995–2015. There is a growing literature on the effects of income inequality on financial crises. This study provides significant evidence in favour of a positive relationship between income i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 91 publications
(239 reference statements)
0
2
0
Order By: Relevance
“…The study by Fasianos et al (2017) contradicted the findings reported by Perugini et al (2016) and Bazillier and Hericourt (2017), as they supported the Rajan hypothesis. Amountzias (2018) studied the inequality crises covering the period 1995-2015 in a panel of 33 OECD countries, following the Minsky hypothesis using a panel VAR framework analysis. Their findings supported a positive relationship between income inequality and financial fragility.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…The study by Fasianos et al (2017) contradicted the findings reported by Perugini et al (2016) and Bazillier and Hericourt (2017), as they supported the Rajan hypothesis. Amountzias (2018) studied the inequality crises covering the period 1995-2015 in a panel of 33 OECD countries, following the Minsky hypothesis using a panel VAR framework analysis. Their findings supported a positive relationship between income inequality and financial fragility.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Some authors find significant evidence in favor of a positive relationship between financial fragility and income inequality in developed countries during the period 1995-2015 [55]. Financial fragility is the opposite to financial resilience, a term that has entered the debate among academics and policymakers in OECD and EU countries [24,56].…”
Section: Financial System's Resilience and Income Inequalitymentioning
confidence: 99%
“…In this paper, we assume that financial resilience can contribute to reducing financial fragility and thus reduce income inequality levels [55].…”
Section: Financial System's Resilience and Income Inequalitymentioning
confidence: 99%